Community Counseling Models Based on Local Wisdom: Strengthening Social Relations in Traditional Communities - Faqihudin Faqihudin (P3M STAI Kuningan, 2024)
Background: Traditional Indonesian communities maintain indigenous counseling practices rooted in local wisdom that prioritize collective harmony and spiritual wellbeing. These healing systems remain underexplored in academic literature, where Western therapeutic assumptions emphasizing individual psychology, confidentiality, and secular approaches dominate.Objective: This study explores lived experiences of traditional counseling based on local wisdom and examines its role in strengthening social relations within Kampung Naga, West Java, Indonesia.Method: A phenomenological study using Interpretative Phenomenological Analysis (IPA) was conducted with twelve participants who experienced traditional counseling addressing social relationship challenges.Findings and Implications: Analysis revealed five superordinate themes representing interconnected mechanisms through which traditional counseling strengthens social relations. The first demonstrates cultural embeddedness through Sundanese cosmology, ritual practices, and Islamic-indigenous syncretism. The second encompasses relational mechanisms including conflict mediation, empathy cultivation, reciprocity restoration, and social identity strengthening. Traditional counseling operates from a holistic, collectivist framework prioritizing community harmony, spiritual wellbeing, and relational restoration over individual psychological adjustment. Findings offer practical implications for mental health professionals by validating indigenous healing systems as legitimate therapeutic alternatives.Conclusion: This research challenges Western therapeutic assumptions about confidentiality and secular approaches while contributing to culturally responsive counseling models that authentically integrate local wisdom with contemporary practice. Findings support decolonizing counseling theory by demonstrating indigenous healing systems' effectiveness in maintaining social cohesion and spiritual wellbeing within traditional communities.